2013
DOI: 10.1001/jamasurg.2013.685
|View full text |Cite
|
Sign up to set email alerts
|

No-Scar Transanal Total Mesorectal Excision

Abstract: To our knowledge, the first pure transanal NOTES total mesorectal excision with retroperitoneal sigmoid mobilization and coloanal, side-to-end anastomosis was successfully performed using what we called a peri-rectal oncologic gateway for retroperitoneal endoscopic single site surgery (PROGRESSS). This monumental case could pave the way for a new era in pure transanal NOTES for colorectal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(20 citation statements)
references
References 25 publications
0
18
0
2
Order By: Relevance
“…123,124 Pure NOTES transanal TME Leroy et al described one of the only two cases of pure NOTES transanal TME done for a preoperatively staged T2 rectal cancer, with final pathology demonstrating a tubulovillous adenoma. 125 Bottom-up mesorectal excision was completed using a rigid metal TES platform, and coloanal handsewn anastomosis was done with no diverting ileostomy. The patient developed a small pelvic hematoma requiring CT-guided drainage.…”
Section: Functional Outcomesmentioning
confidence: 99%
“…123,124 Pure NOTES transanal TME Leroy et al described one of the only two cases of pure NOTES transanal TME done for a preoperatively staged T2 rectal cancer, with final pathology demonstrating a tubulovillous adenoma. 125 Bottom-up mesorectal excision was completed using a rigid metal TES platform, and coloanal handsewn anastomosis was done with no diverting ileostomy. The patient developed a small pelvic hematoma requiring CT-guided drainage.…”
Section: Functional Outcomesmentioning
confidence: 99%
“…Most publications on NOTES have concentrated on short‐term outcomes11, 12, 13, 14. Among studies of colorectal cancer treated with hybrid NOTES, no local recurrence has been reported at 6 months6 24, 25 or 9 months11.…”
Section: Discussionmentioning
confidence: 99%
“…Since the first transgastric liver biopsy by Kalloo and colleagues1, there has been continued interest in natural orifice transluminal endoscopic surgery (NOTES)2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14. For colorectal cancer, most operations have been hybrid procedures4, 5, 6, 7, 8, 9, 10 with few reports11, 12, 13, 14 confined to NOTES alone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have reported pure natural orifice transluminal endoscopic surgery (NOTES) [25,44,45] without an abdominal wound. Intraperitoneal maneuvers, such as high ligation of the inferior mesenteric artery, mobilization of the left colon, etc., are difficult because of the angulation of the promontrium or limitations in the length of the instrument.…”
Section: Future Perspectivementioning
confidence: 99%